(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2018)
Since 2007, the Humanities for Humanity (“H4H”) course has brought together student experience beyond the classroom, educational experiences for community members who could not otherwise attend university, discussion of social justice, and studies in the humanities. By discussing a selection of rich and influential primary texts from the humanities, course members are introduced to a rudimentary history of the present, focussing on who we have become as members of a concrete social and political reality intersected by capitalism, bureaucracy, liberalism, socialism, anti-essentialism, and post-colonialism. Both the texts and the student-participant encounters are rich, and the sessions are guided by two central classical ideals: the activity of learning is primarily an end in itself, and the most important thing to learn may be who we are. The core course content of H4H is outlined, and the ways in which H4H connects student mentors and community participants are discussed. Implications are drawn regarding what makes H4H a unique form of community service-learning in which service is virtually eclipsed by learning in a process that subverts barriers between people.